The monetary economy and the economic crisis - David Laidler (The University of Western Ontario, Economic Policy Research Institute (EPRI), 2010)
The monetary economy has properties that cannot be analyzed using the tools of today's dynamic general equilibrium analysis. Keynes's economics, far from being an aberration in the otherwise orderly evolution of modern macroeconomics from Adam Smith's ideas about the invisible hand, was a major contribution to an ongoing tradition in monetary theory in whose creation Smith himself had played a part. Retrospective consideration of this tradition suggests that the property of the monetary economy critical to the generation of economic crises and the stagnation that follows them is its capacity to permit trading at false prices, a phenomenon ruled out by assumption in dynamic general equilibrium models. Not only Keynes's explanation of depression but also Hayek and Robertson's analysis of the role of unsustainable forced saving in the boom can be thought of as relying on this factor.
Keywords: B12; B22; E12; E13; E32; E40; 330; crises; money; monetary economy; general equilibrium; cycles; sticky prices; flexible prices; false prices; rate of interest; forced saving; Keynesian economics; monetarism; new Keynesian economics; Finanzmarktkrise; Geldpolitik; Preisrigidität; Zins; Keynesianismus; Theorie